KEBERADAAN HARTA PERKAWINAN DALAM PROBLEMATIKA PERKAWINAN - Isetyowati Andayani (Perspektif, 2005)
Keeping house a lot of happened the problematical faced by husband and wife, what as a result cannot maintain the everlasting domesticity Break the marriage can be happened because death, divorce and justice decision. While breaking marriage of because divorce, sure a lot of generating problems to “Their Marriage Estae”.